2017
DOI: 10.1088/1361-6463/aa5616
|View full text |Cite
|
Sign up to set email alerts
|

An overview of CO2conversion in a microwave discharge: the role of plasma-catalysis

Abstract: An overview of the recent progress on plasma-assisted CO2 conversion in microwave discharges is given. Special attention is devoted to the results obtained using plasma catalysis, which are compared to the plasma-only CO2 decomposition cases. The effects of plasma operating conditions, catalyst preparation methods, nature of plasma activation gas, gas mixture, as well as the NiO content on the TiO2 surface on CO2 conversion and its energy efficiency are discussed. A significant improvement in CO2 conversion is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
56
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4
1

Relationship

3
6

Authors

Journals

citations
Cited by 77 publications
(61 citation statements)
references
References 47 publications
5
56
0
Order By: Relevance
“…A relatively small number of experiments were performed until the 1980's when there was a rapidly increasing number of reports motivated by the potential of plasma-catalysis to provide an efficient and sustainable process for a range of environmental, chemical and energy-related processes [4]. Recent review articles on plasma-catalysis will give a flavour of the range and nature of current research [1,[5][6][7][8][9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…A relatively small number of experiments were performed until the 1980's when there was a rapidly increasing number of reports motivated by the potential of plasma-catalysis to provide an efficient and sustainable process for a range of environmental, chemical and energy-related processes [4]. Recent review articles on plasma-catalysis will give a flavour of the range and nature of current research [1,[5][6][7][8][9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…In relation to microwave plasmas, Chen et al reported that placing a NiO/ TiO 2 catalyst in the downstream of a low-pressure microwave plasma significantly increased the CO 2 conversion efficiency and energy efficiency [25,28]. They concluded that the oxygen vacancies provide the sites for adsorption of oxygen atoms from CO 2 .…”
Section: Mw Regionmentioning
confidence: 99%
“…Motivated by the previously mentioned strategy, numerous research groups are currently focused on achieving the maximum conversion and energy efficiencies (defined in the following chapters) associated to the CO 2 decomposition via modeling [10,11] as well as through the experimental studies [12][13][14][15]. In addition to the plasma itself, utilization of the pre-activated highly porous catalyst may also significantly increase the energy efficiency of the conversion process, as shown in the numerous literature sources [16,17] and demonstrated in this book.…”
Section: How Does It Work?mentioning
confidence: 99%